In Vivo Blockade of Murine ARTC2.2 During Cell Preparation Preserves the Vitality and Function of Liver Tissue-Resident Memory T Cells - Rissiek, Björn; Lukowiak, Marco; Raczkowski, Friederike; Magnus, Tim; Mittrücker, Hans-Willi; Koch-Nolte, Friedrich (Frontiers in Immunology, 2018)
On murine T cells, GPI-anchored ADP-ribosyltransferase 2.2 (ARTC2.2) ADP-ribosylates the P2X7 ion channel at arginine 125 in response to nicotinamide adenine dinucleotide (NAD+) released during cell preparation. We have previously shown that chronic gating of P2X7 by ADP-ribosylation reduces the vitality and function of regulatory T cells (Tregs) and NKT cells that co-express high levels of ARTC2.2 and P2X7. Here, we evaluated the expression of ARTC2.2 and P2X7 by effector and memory T cells in the liver of naïve mice and after infection with Listeria monocytogenes (Lm). We found that KLRG1–/CD69+ tissue-resident memory T cells (Trm) in the liver of naïve mice and seven weeks after infection with Lm express high levels of ARTC2.2 and P2X7. Isolation of liver Trm and subsequent incubation at 37 °C resulted in cell death of the majority of CD4+ and CD8+ Trm. Injection of the ARTC2.2-blocking nanobody s+16a 30min prior to organ harvesting effectively prevented ADP-ribosylation of P2X7 during cell preparation and thereby prevented NAD-induced cell death (NICD) of the isolated Trm upon subsequent incubation at 37 °C. Consequently, preserving Trm vitality by s+16a injection enabled a highly sensitive in vitro cytokine expression profile analyses of FACS sorted liver Trm. We conclude that in vivo blockade of ARTC2.2 during cell preparation by nanobody s+16a injection represents a valuable strategy to study the role and function of liver Trm in mice.